Optimalisasi Kemandirian Lansia dengan Penyakit Kronis dalam Penurunan Tingkat Kecemasan melalui Terapi Mindfulness - Ni Komang Sukra Andini; Sang Ayu Ketut Candrawati; Ni Ketut Citrawati; Ni Ketut Ayu Mirayanti; Putu Gede Subhaktiyasa (Al-Qalam Institute, 2023)
Elderly with chronic disease in Indonesia has a fairly high number. As many as 28.53% of elderly aged 60-69 years have health complaints related to chronic diseases. This percentage continues to increase in older age groups. Chronic disease can have an impact on the health of the elderly, in this case mental health, namely anxiety. Anxiety management is an effort to deal with disturbing anxiety but does not mean eliminating anxiety, but reducing it so that it does not create obstacles for someone in living their life. Anxiety can also be used as a motivation for someone to be better and positive. One of the popular complementary therapies for dealing with anxiety is mindfulness meditation. The method is carried out with lectures, discussions and simulations via video with the elderly.